Invasion of fall armyworm Spodoptera frugiperda, a new invasive pest, alters native herbivore attack intensity and natural enemy diversity (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rizali A, Oktaviyani, Putri SDPS, Doananda M, Linggani A. 2021. Invasion of fall armyworm Spodoptera frugiperda, a new invasive pest, alters native herbivore attack intensity and natural enemy diversity. Biodiversitas 22: 3482-3488. A new invasive alien pest, fall armyworm Spodoptera frugiperda has been reported widely spread in Indonesia since 2019 and can cause a serious problem in maize cultivation. Its invasion of new habitat may severely impact not only maize production but also native biodiversity including other native pests. This research was aimed to investigate the effect of S. frugiperda invasion on the attack intensity of native herbivores as well as the diversity of natural enemies in maize fields. Field research was conducted in twelve maize fields spread across the district of Malang, Kediri, and Batu, East Java, Indonesia. In each maize field, sampling of S. frugiperda and other insects was conducted by the hand-picking method within four transects with each transect consisting of 100 plants. The results found five species of lepidopteran pests including S. frugiperda, Ostrinia furnacalis, Helicoverpa armigera, Mycalesis sp, and Chrysodeixes sp. S. frugiperda was found with higher attack intensity than other lepidopteran pests. Based on the analysis, the attack intensity of S. frugiperda had a positive relationship with pesticide application and was marginally correlated with plant age and elevation. The infestation of S. frugiperda significantly reduced the attack intensity of other lepidopteran pests as well as the diversity of natural enemies, especially predators. Two native species of parasitoid wasps, Telenomus sp and Mymaridae sp were recorded parasitizing the eggs of S. frugiperda. In conclusion, the infestation of S. frugiperda causes biotic homogenization in the maize field by directly compete with other lepidopteran pests and indirectly eliminate the natural enemy diversity.
Keywords: invasive species; maize field; lepidopteran pest; parasitoid; predator